Striving towards sustainability: integrating environmental concerns into the political bioeconomy discourse? - Kleinschmit, A. Daniela; Giurca, Alexandru; Mustalahti, Irmeli; Sergent, E. Arnaud; Pülzl, Helga (Natural Resources Institute Finland, Luke, 2016)
Sustainable development (SD) is highlighted in different strategies as the overarching goal of the shift towards bioeconomy. Understanding how sustainable development (SD) is approached in the political discourse of bioeconomy is the main objective of this paper. This paper focuses on the ecological perspective of SD and analyses whether and how environmental concerns are integrated into the political bioeconomy discourse of the EU and four of its member states: Germany, Finland, France and the Netherlands. It is found that the political bioeconomy discourse does not strive to give priority to environmental concerns.
Keywords: bioeconomy; sustainable development; environmental policy integration; EU; forest sector